DAMPAK KELEBIHAN KAPASITAS WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KLAS II A PEKANBARU DIKAITKAN PEMENUHAN HAK-HAK WARGA BINAAN BERDASARKAN PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA REPUBLIK INDONESIA NOMOR M.HH-07.OT.01.03 TAHUN 2011 - Lestari S, Selly Dian; Indra, Mexsasai; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The impact of overcapacity inmates at the Correctional Institution Class II A Pekanbaru associated fulfillment of the rights of inmates based on the Minister of Justice and Human Rights of the Republic of Indonesia Number M.HH-07.OT.01.03 in 2011. Efforts made in dealing with the impact of overcapacity inmates at the Correctional Institution Class II A Pekanbaru associated fulfillment of the rights of inmates based on the Minister of Justice and Human rights of the Republic of Indonesia Number M.HH-07.OT.01.03 in 2011. This research method is a sociological study. That is reviewing the state of the existing problems in the field associated with the legal aspects that prevail in society. Where to see how it will impact the excess capacity in the Prison Class II A Pekanbaru. The results of the study authors obtained can be concluded. The first impact of overcapacity Penitentiary as kriminogenik factors that have an impact on the security side where the circumstances lead to difficulty the prisoners to get their rights. Second, that the efforts made in addressing the impact of the excess capacity of the Penitentiary Class II A Pekanbaru with accelerating speed up the development of social reintegration efforts.Keywords: Overcapacity-Patronage-Fulfillment Citizens Rights